PENGEMBANGAN PEMBELAJARAN SENAMMELALUI BERMAIN DI SEKOLAH DASAR - Fredericus Suharjana (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2011)
Child living cannot be separated from playing. For child, playing is a means for exercising to be adult to develop hisinner potential. Teaching of physical education, sport and health implemented in primary school must be served inthe form of game so that child is eager to do the activity joyfully, and so with the gymnastics material. Gymnasticsis one of the physical education, sport and health in primary school which for part of children does not like with theexistence of it due to its difficultness, enough high risk of injured, so it seems to be frightened. Physical educationteacher must be aware that gymnastics education presented in schools is not competitive gymnastics, so it ismerely used as a means to achieve the aim of education. Thus its upmost aim is not his skill, but the child himselfis. Let the child grows in accord with his own capability. Give him as many chances as possible to move and to growin line with his ability. For the child is eager to do the gymnastics joyfully, present the gymnastics in the form ofgame, and guide him in line with his capability. Learning of gymnastics for primary school child is a means toachieve overall development, includes: physical, mental, social, emotional and moral. Gymnastics educationaims to enrich movement experience as much as possible and to increase students’ physical fitness.Keywords: playing, teaching, gymnastics and physical education.Abstract :Hidup anak tidak dapat dipisahkan dari bermain. Untuk anak, bermain adalah sarana untuk berolahragamenjadi dewasa untuk mengembangkan potensi batinnya. Pengajaran pendidikan jasmani, olahraga dankesehatan dilaksanakan di sekolah dasar harus disajikan dalam bentuk permainan sehingga anak yang inginmelakukan aktivitas dengan sukacita dengan materi senam. Senam adalah salah satu dari materi dalamolahraga, pendidikan jasmani dan kesehatan di sekolah dasar yang bagi sebagiananak anak tidak suka dengankeberadaan itu karena kesulitannya, risiko yang cukup tinggi dari cedera, sehingga tampaknya menjadi takut.Guru pendidikan jasmani harus sadar bahwa senam pendidikan yang disajikan di sekolah tidak senamkompetitif, sehingga hanya digunakan sebagai sarana untuk mencapai tujuan pendidikan. Jadi tujuannyatidak maksimal keterampilan, tapi anak sendiri. Biarkan anak tumbuh sesuai dengan kemampuan sendiri.Berikan dia sebagai kesempatan sebanyak mungkin untuk bergerak dan tumbuh sejalan dengankemampuannya. Untuk anak ingin melakukan senam gembira, sekarang senam dalam bentuk permainan,dan membimbingnya sesuai dengan kemampuannya. Belajar senam untuk anak sekolah dasar merupakansarana untuk mencapai pembangunan secara keseluruhan, meliputi: fisik, mental, sosial, emosional danmoral. Senam pendidikan bertujuan untuk memperkaya pengalaman gerakan sebanyak mungkin dan untukmeningkatkankebugaran fisik siswa.